A Multistate Kalman Filter for Neonatal Clotting Time Prediction and Early Detection of Coagulation Disturbances - de Haan, A. F. J.; van der Velde, J.; Geven, W. B.; Festen, C.; Verbeek, A. L. M. (Methods of Information in Medicine, 1999)
The multistate Kalman filter was applied to develop a heparin dose proposal system and to detect coagulation disturbances during neonatal extracorporeal membrane oxygenation (ECMO). A system containing this filter was based on the activated clotting time (ACT) values and the heparin doses administered every hour during ECMO. If the ACT value can be predicted accurately from the previous heparin dose, a heparin dose proposal can be given to achieve or maintain the required ACT level. The analysis was done on 6,356 ACT level measurements in 44 ECMO neonates. The multistate Kalman filter technique showed an unbiased prediction of ACT, with a standard deviation of 23 seconds. Two out of three cases of disseminated intravascular coagulation (DIC) were detected. ACT values were predicted sufficiently accurately by the multistate Kalman filter technique to justify a prospective study on the performance of the heparin dose proposal system and its ability to detect DIC.
Keywords: Multistate Kalman Filter; Extracorporeal Membrane Oxygenation; Computer-aided Monitoring